Triggers for de-compensation of Chronic Liver Disease in South of Lahore - Hafiz Hamad Ashraf, Sehrish Sarwar, Azhar Ali Khan, Osama Habib, Sidra Mehdi, Shahzad Ashraf, Ambar Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cirrhosis is a leading cause of mortality and morbidity across the world with cases number estimated to be as high as 1.5 Billion. Pakistan is one of the countries where the burden of disease is significantly high. Aim: To understand potential causative factors contributing towards decompensation of liver disease and report it for the benefit of other units providing service to similar population. Study design: Prospective observational study Methods: Common complications of portal hypertension resulting from chronic liver disease include development of ascites, encephalopathy, GI bleeding and hepato-renal syndrome. Decompensation of cirrhosis can be transient with full recovery (re-compensation), or it can be chronic. During an event of acute decompensation, clinicians strive to treat the underlying trigger which may have resulted in decompensation alongside the supportive treatment. Several of such potential factors have been reported in the literature. New infection, dehydration, consumption of alcohol and new medications are a few to mention. Many a times the cause of decompensation remains unclear. Results: The patients with established cirrhosis can develop such complications of the disease resulting in what is known as decompensation at any point during disease. It is imperative for a liver unit to know the relevant causes of hepatic decompensation in its own patients so that the treatment is based on the evidence from local population; the data which is scarce. Conclusion: Non-compliance with medical advice was the commonest factor as opposed to the available data most of which reports infection as the commonest factor, although infection was the second most common factor, and the commonest concomitant factor in this subset of patients. Cause of decompensation remains unidentified in over one fourth of cases.